Improvement of a Magnus VAWT Based on Numerical Simulation using a Fixed Blade - Dyusembaeva, A.; Tanasheva, N.; Sarzhanova, I.; Bakhtybekova, A.; Tleubergenova, A.; Abdirova, N.; Shuyushbayeva, N. (CFD Letters, 2025)
Magnus wind turbines have a wide range of advantages ranging from generating energy at low wind speeds to adapting to any wind direction. However, the cylindrical blades themselves have high drag and low lift. The aim of the work is to study the addition of a fixed blade to the cylindrical blades of a wind turbine to improve the efficiency of the entire wind turbine. The paper presents a numerical study of the lifting force and drag force of a wind turbine, as well as the blades themselves, averaged over time from the air flow velocity and the number of revolutions. Using the averaging method of the Navier-Stokes equations RANS (Reynolds-averaged Navier–Stokes), numerical results were obtained showing the efficiency of the installation starting from 3 m/s, i.e. low wind speeds. It is determined that the use of adding a fixed blade to a rotating cylinder gives an increase in the value of the lifting force from 40-55% and power factor of the wind turbine by almost 1.5-1.7 times due to the regulation and reduction of the disruption of vortices behind the rotating cylinder. The effect of the plate on the velocity and pressure field is illustrated. The results obtained are useful when designing real experimental installations.
Keywords: Magnus; wind turbine; fixed blades; cylinder; numerical simulation